Gramàtica, interacció i organització informativa en el discurs oral - Castellà Lidon, Josep M. (Caplletra. Revista Internacional de Filologia, 2008)
This article deals with some grammar aspects of oral language, which includes an extense sense of the concept of grammar itself. The linguistic characteristics of orality are studied in relation to the physical, cognitive and sociopragmatic factors that intervene in speech’s production and reception. The specific grammaticalelements that are presented, in a panoramic vision, are the tonal unit, basic unit of oral speech; the informative progression and the RUT restriction; the grammatical categories and the verbal style; the role of subordination in clausal composition; and, to conclude, the nature and the function of textual connectors in the organization of oral discourse. On the whole, a contribution to the explanation of the mobile, diverse, polyvalent and complex nature of the oral language is attempted.